Primary Lymphoma of the Gynecologic Tract: A Comprehensive Pathologic Analysis of 15 Cases - Haneen Al-Maghrabi; Jaudah Al-Maghrabi (Diagnostics)
Background: Diagnoses of primary gynecologic (GYN) lymphomas are rare and require a high clinical index of suspicion, with only case reports and case series being presented. The aim of this study is to assess and record the pathological distinction of primary GYN lymphomas at two tertiary hospitals. Materials and Methods: We retrieved all cases diagnosed from 2000 to 2024, reviewed histopathology slides, and performed additional extra immunohistochemistry staining for required cases. In addition, follow-up information available up to the point of writing this study was gathered. Results: The records of two hospitals indicated 15 instances of primary GYN lymphoma in patients aged between 18 and 79. Only one patient was human immunodeficiency virus (HIV)-positive. Symptoms in most cases were non-specific, and most of the patients presented with the primary complaint of unexplained bleeding. A total of 13 cases were classified as diffuse large B-cell lymphoma (DLBCL), 1 as acute B-lymphoblastic lymphoma (B-LBL), and 1 as Burkitt lymphoma (BL). Conclusions: Primary lymphoma of the GYN tract is a rare disease, with DLBCL being the most prevalent type in our area. Our review, based on experiences from two large tertiary centers in the western region of Saudi Arabia, aims to contribute to this effort. The reporting of additional cases of primary GYN lymphoma is needed, which may aid in a better understanding of its pathogenesis as well as enhancing diagnosis and treatment outcomes.